Systematic Literature Review: Digital Financial and MSME Performance in Indonesia - Chandra Satria; Doly Nofiansyah; Bagus Dwi Cahya (Fakultas Studi Islam Universitas Islam Kalimantan Muhammad Arsyad Al Banjary, 2024)
The aim of this study is to examine trends and developments in research related to digital financials and the performance of small and medium-sized microenterprises in an effort to improve the economy of small and medium-sized enterprises in Indonesia. Digital Financial research bibliometric data is taken from secondary data via the Publish or Perish application search engine version 8 with the search engine option feature of the Google Scholar application menu. The study finds information about how many research articles and keywords are used, the number of publishers, as well as the reputation rankings of any journal that publishes digital financial and micro and medium enterprises. Performance themes; the year trend begins to emerge and the majority of queries on digital financial and micro enterprises performance; the implications generated by previous investigations related to Digital Financial, and the performance of micro and small enterprises; the impact of digital financial withdrawal by micro and medium enterprises can face uncertain global economic challenges; the role of Digital Financial can enhance financial inclusion; the government has an important and vital role in formulating policies related to the development of the digital financial ecosystem Micro Small Medium Enterprises (MSME) ; the implementation of Digital Finance is well implemented by the Micro Finance Institutions to accelerate the positive performance of MSME.